Survey on Mobile Ad hoc Network Performance Using Upper Threshold RED (International Journal of Scientific Research and Management (IJSRM), 2015)
Random Early Detection [RED] algorithm achieves high throughput, packet delivery and low average delay by stabilizing the average queue size through mapping the congestion into packet drop probability and detection and avoidance of incipient congestion. In most cases RED performance is sensitive to its parameter setting. In this paper proposed algorithm has introduce the new threshold parameter (Uth) to reduce sensitivity of RED on its parameter setting, so that its performance will improve. Goal of this paper is propose a new mechanism to achieve high throughput and low end to end delay in congested network.